Konsep Islam Moderat Dalam Al-Qur’an - Hamzah (LP2M Universitas PTIQ Jakarta, 2019)
The era of globalization which is expected to be the era of the formation of a community of ”groups”, apparently leaves many problems, including: First, the clash of civilizations between large human groups. Secondly, it creates uneven competition between large groups and small groups. Facing this reality, Muslims are required to be moderate. The question is how is the concept of moderation in accordance with the values of the Qur’an? Using a thematic interpretation method, this paper concludes that Muslim moderation must be able to integrate two different patterns of relationships; pattern of relationship with God and pattern of relationship with humans. Moderate cannot be interpreted as a hard attitude, or a very free understanding without limits. A true moderate attitude is able to bring about world peace, without violence and the goodness of the afterlife.